2021
DOI: 10.21203/rs.3.rs-222041/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carbapenem-Resistant Enterobacter cloacae Complex in a Tertiary Hospital in Northeast China, 2010-2019

Abstract: Background: Carbapenem-resistant Enterobacter cloacae complex (CREC) is a new emerging threat to global public health. The objective of the study was to investigate the clinical characteristics and molecular epidemiology of CREC infections in the medical center of northeast China.Methods: Twenty-nine patients were infected/colonized with CREC during a ten-year period (2010-2019) by WHONET analysis. Antibiotic susceptibilities were tested with VITEK 2 and micro broth dilution method (for polymyxin B and tigecyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Globally, bla CHβLs such as bla KPC (class A), bla NDM/VIM/ IMP (class B) and bla OXA-48 (class D) are of grave clinical concern and proliferating [8]. It was reported that bla NDM-1 and bla NDM-5 were the main bla CHβLs , ST93, ST171 and ST145 was the predominant sequence types (STs) for CREL in a tertiary Hospital in Northeast China during 2010-2019 [9]. Whereas in Japan, bla IMP-1 was the dominant bla CHβLs conferring carbapenem resistance [10], and bla VIM was the main bla CHβLs in France between 2015-2018 [11].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, bla CHβLs such as bla KPC (class A), bla NDM/VIM/ IMP (class B) and bla OXA-48 (class D) are of grave clinical concern and proliferating [8]. It was reported that bla NDM-1 and bla NDM-5 were the main bla CHβLs , ST93, ST171 and ST145 was the predominant sequence types (STs) for CREL in a tertiary Hospital in Northeast China during 2010-2019 [9]. Whereas in Japan, bla IMP-1 was the dominant bla CHβLs conferring carbapenem resistance [10], and bla VIM was the main bla CHβLs in France between 2015-2018 [11].…”
Section: Introductionmentioning
confidence: 99%